2021
DOI: 10.3390/ijms22041614
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomics Unveil Possible Transposable Elements Driving Rearrangements in Chromosomes 2 and 4 of Solea senegalensis

Abstract: Cytogenomics, the integration of cytogenetic and genomic data, has been used here to reconstruct the evolution of chromosomes 2 and 4 of Solea senegalensis. S. senegalensis is a flat fish with a karyotype comprising 2n = 42 chromosomes: 6 metacentric + 4 submetacentric + 8 subtelocentric + 24 telocentric. The Fluorescence in situ Hybridization with Bacterial Artificial Chromosomes (FISH-BAC ) technique was applied to locate BACs in these chromosomes (11 and 10 BACs in chromosomes 2 and 4, respectively) and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Among vertebrates, there are qualitative and quantitative differences in TEs: Class I retrotransposons are the most abundant group in mammalian and avian genomes; and Class II DNA transposons are the most abundant transposable element in fish genomes [ 77 ]. Our results have shown that TE content in hox clusters is lower than whole genome coverage values [ 13 , 15 , 17 ] except in the hoxba cluster, where we have reported, as in the lizard species, an increased accumulation of interspersed repeats comprised mainly retrotransposons [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Among vertebrates, there are qualitative and quantitative differences in TEs: Class I retrotransposons are the most abundant group in mammalian and avian genomes; and Class II DNA transposons are the most abundant transposable element in fish genomes [ 77 ]. Our results have shown that TE content in hox clusters is lower than whole genome coverage values [ 13 , 15 , 17 ] except in the hoxba cluster, where we have reported, as in the lizard species, an increased accumulation of interspersed repeats comprised mainly retrotransposons [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 71%
“…The repeat elements analyzed were transposable elements (TEs) (Class I and II), simple repeats, satellite sequences, low-complexity elements and small RNA. The parameters used to measure the abundance of repeated elements of each hox cluster were the number of loci per Mb (NL/Mb) and their coverage, measured as a percentage of length occupied by repeated elements per cluster analyzed (%) [ 13 , 15 ]. To study the distribution of repetitive elements throughout the hoxba cluster, a sliding window of 3 kb was applied using TE annotations from RepeatMasker results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, we carried out the study of abundance by chromosomes, considering that they could have a seemingly more local behavior, like an ecosystem, and reflect their evolution. In previous studies, partial analyses of the distribution of repetitive elements in S. senegalensis have been carried out by analyzing the content of these elements in BAC clones located in cytogenetic maps (Rodrıǵuez et al, 2019, Rodrıǵuez et al, 2021Ramıŕez et al, 2022). In these studies, clones (between 4 and 8) were analyzed, spaced out in some chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Senegalese sole (Solea senegalensis) is among the most important flatfish, with a wide distribution along the eastern coast of the Atlantic Ocean and in the Mediterranean Sea and a high economic value (Imsland et al, 2004;Dıáz-Ferguson et al, 2007, Dıáz-Ferguson et al, 2012. This commercial interest has promoted the increase in genomic resources in the last decade (Robledo et al, 2017;Garcıá-Angulo et al, 2018;Cross et al, 2020;Merlo et al, 2021;Rodrıǵuez et al, 2021;de la Herrań et al, 2023), including an initial version of its genome (Guerrero-Coźar et al, 2021) and a recent improved version (de la Herrań et al, 2023). Due to the absence, until 2023, of a quality sequenced genome in this species, repetitive sequence studies on Senegalese sole had been limited to the sequence analysis of some BAC clones mapped on the chromosomes of the species (Garcıá et al, 2019;Rodrıǵuez et al, 2019;Cross et al, 2020;Rodrıǵuez et al, 2021;Ramıŕez et al, 2022) and the study of TEs in the Hox gene clusters of three flatfish species, including S. senegalensis (Mendizabal-Castillero et al, 2022).…”
Section: Introductionmentioning
confidence: 99%